Pengaruh Debt to Equity Ratio, Assets Growth dan Inventory Turnover terhadap Return on Assets Pada PT Hero Supermarket Tbk Periode 2012-2023 - Yojana, Dery Hafizh Janitra; Priyanto, Aria Aji (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
The purpose of this study is to examine the established hypothesis regarding the impact of the debt to equity ratio, asset growth, and inventory turnover on return on assets at PT Hero Supermarket Tbk for the period 2012-2023. The research method used is a quantitative approach with an associative problem formulation, which seeks to investigate the relationship between two or more variables. This method is employed to test and determine the effect of the debt to equity ratio, asset growth, and inventory turnover on return on assets, both partially and simultaneously, at PT Hero Supermarket Tbk for the period 2012-2023. The results of this study indicate that the debt to equity ratio does not affect return on assets. Asset growth does not affect return on assets. Inventory turnover does not affect return on assets. Furthermore, the debt to equity ratio, asset growth, and inventory turnover simultaneously do not affect return on assets.